Study of Bioclimatic Architecture as A Basis for The Formation of A Sports Center in Batu City - Abdul Rohman; Febby Rahmatullah Masruchin; Retno Hastijanti (Kirana Publisher (KNPub), 2026)
This study examines bioclimatic architecture as the basis for developing a Sport Center in Batu City. The city’s mountain climate, moderate temperatures, and favorable natural ventilation potential provide an opportunity to implement climate-responsive design. This research used a descriptive qualitative approach through literature review, climatic analysis, and evaluation of sports facility requirements. The findings indicate that building orientation, cross ventilation, solar control, vegetation integration, daylight utilization, and environmentally friendly materials can significantly improve thermal comfort while reducing energy consumption. The proposed Sport Center concept emphasizes adaptation to local climate conditions and sustainable architectural strategies. The study concludes that bioclimatic architecture can serve as an effective design framework for sports facilities in Batu City because it enhances environmental performance, user comfort, and long-term sustainability. The results provide a reference for planners, architects, and local governments in developing energy-efficient sports infrastructure.